Analysis of deep stress field using well log and wellbore breakout data: a case study in Cretaceous oil reservoir, southwest Iran - Abdideh, Mohammad; Alisamir, Sina (Geodesy and Cartography, 2018)
To identify the wellbore instability of Bangestan oil reservoir in the southwestern Iran, the direction and magnitude of stresses were determined using two different methods in this study. Results of injection test and analysis of wellbore breakouts were used to verify the accuracy of the stress profiles. In this study the Bartoon method, which using the breakout angle and strength of rock, was used. In addition, the ability of artificial neural network to estimate the elastic parameters of rock and stress field was used. The output of the neural network represents a high accuracy in the estimation of the desired parameters. In addition, the Mohr-Coulomb failure criterion was used to verify stress profiles. Estimated stresses show relative compliance with the results of injection test and Barton method. The required minimum mud pressure for preventing shear failures was calculated by using the Mohr-Coulomb failure criterion and the estimated stress profiles. The results showed a good compliance with failures which have been identified in the caliper and image logs. However, a number of noncompliance is observed in some depth. This is due to the concentration of fractures, collisions between the drill string and the wellbore wall, as well as swab and surge pressures. The stress mode is normal and strike-slip in some depth based on the estimated stress profiles. According to direction of breakouts which is clearly visible in the caliper and image logs, the minimum and maximum horizontal stresses directions were NW-SE and NE-SW, respectively. Thses directions were consistent with the direction of regional stresses in the Zagros belt.